Clinton's Cuba policy : a low-priority dilemma. - LANDAU, Saul (1993)
Asserts that the battle over Cuba policy is being waged largely outside of government circles. To change current policy, alternative effective domestic constituencies need to materialize to challenge the powerful Miami-based Cuban American National Foundation (CANF).